Shouldice Hospital: Dedicated to the Repair of Hernias - Stobie, Beth (Operating Room Nurses Association of Canada Journal, 1999)
Dr. Earle Shouldice founded the Shouldice Hospital, a private facility dedicated to the repair of hernias, in 1945. The first hospital opened in a converted house on Church Street in Toronto with a single operating room. As requests for his unique surgery increased, he bought the three adjacent buildings. Finally, in 1953 he purchased a beautiful country estate North of Toronto in Thornhill, and a second hospital was established. In 1969 an eighty-nine bed facility, designed to encourage maximum ambulation and minimize the atmosphere that patients associate with hospitals, was opened at the Thornhill site, and the downtown hospital was closed.